Pengaruh Aribut Produk Dan Brand Awareness Terhadap Keputusan Pembelian - Amin Hou (LPPM dan Fakultas Ekonomi dan Bisnis Universitas Kahuripan Kediri, 2021)
The focus of the main objective of this study is to determine the effect of product attributes and brand awareness on consumer purchasing decisions at PT. Indah Sakti Motorindo. This type of research is quantitative research. The population is consumers at PT. Indah Sakti Motorindo, totaling 129 people, of which 72 people were sampled with random sampling technique. The results showed that partially both product attribute variables and brand awareness had a positive and significant effect on purchasing decisions. The most dominant variable in influencing purchasing decisions is the brand awareness variable.